On matricide : myth, psychoanalysis, and the law of the mother - Jacobs, Amber (Columbia University Press, 2007)
Despite advances in feminism, the ""law of the father"" remains the dominant model of Western psychological and cultural analysis, and the law of the mother continues to exist as an underdeveloped and marginal concept. In her radical rereading of the Greek myth, Oresteia, Amber Jacobs hopes to rectify the occlusion of the mother and reinforce her role as an active agent in the laws that determine and reinforce our cultural organization. According to Greek myth, Metis, Athena's mother, was Zeus's first wife. Zeus swallowed Metis to prevent her from bearing children who wou.